1997
DOI: 10.1021/ja964420t
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the Synthesis of the Vancomycin Antibiotics. Synthesis of Orienticin C (Bis-dechlorovancomycin) Aglycon

Abstract: In the preceding paper, we described the synthesis of the vancomycin-related M(4-6)(5-7) bicyclic subunit 3 (Scheme 1), 1,2 a structural motif common to all members of this family of antibiotics exemplified by vancomycin aglycon (1). 3 Herein we describe the first synthesis of the vancomycin-related heptapeptide nucleus and the transformation of this intermediate to orienticin C (bis-dechlorovancomycin) aglycon (2). 4Our original strategy for the construction of the biaryl ethercontaining rings was based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
77
1
4

Year Published

1998
1998
1998
1998

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 19 publications
0
77
1
4
Order By: Relevance
“…Use of Li 2 CO 3 in MeOH minimized this side reaction and provided 8 b, which was used in unpurified form after aqueous workup. Following Boc cleavage, coupling of 8 a and 8 b to amino acid 5 and subsequent protecting group exchange afforded tripeptides Oxidative cyclization of 10 a and 10 b according to our previously reported conditions (VOF 3 ) [9,10] provided the M(5 ± 7) cyclic tripeptides 11 a and 11 b as their unnatural R atropisomers (dr b 95:5). The reductive quench for this oxidation was modified to employ NaBH(OAc) 3 in place of zinc dust to avoid the unwanted reduction of the nitro group in ring 6.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Use of Li 2 CO 3 in MeOH minimized this side reaction and provided 8 b, which was used in unpurified form after aqueous workup. Following Boc cleavage, coupling of 8 a and 8 b to amino acid 5 and subsequent protecting group exchange afforded tripeptides Oxidative cyclization of 10 a and 10 b according to our previously reported conditions (VOF 3 ) [9,10] provided the M(5 ± 7) cyclic tripeptides 11 a and 11 b as their unnatural R atropisomers (dr b 95:5). The reductive quench for this oxidation was modified to employ NaBH(OAc) 3 in place of zinc dust to avoid the unwanted reduction of the nitro group in ring 6.…”
mentioning
confidence: 93%
“…Application of this methodology to the synthesis of bis-dechlorovancomycin (orienticin C) aglycon has recently been reported. [10] The most formidable synthesis challenges that the vancomycin skeleton presents are the three stereochemical elements of atropisomerism present in the structure as a consequence of hindered rotation in each of the cyclic tripeptide subunits. Our recent efforts have been directed toward the development of strategies for controlling these architectural features during the assemblage of the vancomycin skeleton.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these three features of the aglycon architecture present the significant challenge of controlling atropisomerism in the construction of each of the three macrocyclic tripeptide subunits designated as M(2 ± 4), M(4 ± 6), and M(5 ± 7). [5] Hence, even with asymmetric syntheses of the amino acid constituents [6] and an assemblage strategy in hand, [7] one is still faced with the problem of producing the vancomycin aglycon skeleton as only one of eight possible atropdiastereomers.…”
mentioning
confidence: 99%
“…[9,10] This stereochemical bias also extends to the more complex oxidative cyclization found in the orienticin C synthesis (Scheme 1 b). [7] A(1,3) strain [11] was implicated as the stereochemical control element in these cyclizations when it was found that the diastereomeric tripeptide 6, containing the epimeric arylglycine in position 5, underwent a highly diastereoselective oxidative ring closure to the natural atropisomeric product 7 with S configuration.…”
mentioning
confidence: 99%